2017
DOI: 10.1021/acschemneuro.7b00096
|View full text |Cite
|
Sign up to set email alerts
|

The Marine Guanidine Alkaloid Crambescidin 816 Induces Calcium Influx and Cytotoxicity in Primary Cultures of Cortical Neurons through Glutamate Receptors

Abstract: Crambescidin 816 is a guanidine alkaloid produced by the sponge Crambe crambe with known antitumoral activity. While the information describing the effects of this alkaloid in central neurons is scarce, Cramb816 is known to block voltage dependent calcium channels being selective for L-type channels. Moreover, Cramb816 reduced neuronal viability through an unknown mechanism. Here, we aimed to describe the toxic activity of Cramb816 in cortical neurons. Since calcium influx is considered the main mechanism resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…However, at higher concentrations MTX3, in contrast to gambierone, caused a decrease in cell viability in undifferentiated neuroblastoma cells opening the door to further explore its putative therapeutic effects (for example in glioma treatment). In fact, the marine compounds crambescidins induced moderate rises in neuronal cytosolic calcium through activation of ionotropic glutamate receptors [46] and have a profitable activity inhibiting tumor growth [47]. Interestingly, chronic exposure of human neurons to either gambierone or MTX3 modified the expression of excitatory neurotransmiter receptor subunits, an alteration that was observed also after exposure of mice cortical neurons to CTX3C [37] and that could be involved in the neurological symptoms caused by ciguatera in humans [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at higher concentrations MTX3, in contrast to gambierone, caused a decrease in cell viability in undifferentiated neuroblastoma cells opening the door to further explore its putative therapeutic effects (for example in glioma treatment). In fact, the marine compounds crambescidins induced moderate rises in neuronal cytosolic calcium through activation of ionotropic glutamate receptors [46] and have a profitable activity inhibiting tumor growth [47]. Interestingly, chronic exposure of human neurons to either gambierone or MTX3 modified the expression of excitatory neurotransmiter receptor subunits, an alteration that was observed also after exposure of mice cortical neurons to CTX3C [37] and that could be involved in the neurological symptoms caused by ciguatera in humans [4].…”
Section: Discussionmentioning
confidence: 99%
“…The light source was a xenon arc bulb and the excitation wavelengths were selected with filters. Excitation wavelengths were 340 and 380 nm, and the emission was collected at 510 nm [46]. Data were analyzed with the Metafluor software (version 7.1, Molecular Devices, LLC, Sunnyvale, CA, USA) and expressed as the 340/380 fluorescence ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Primary cortical neurons were obtained from embryonic day 16−18 Swiss mice following previously described procedures [ 14 , 17 , 26 , 36 ]. All protocols were approved by the University of Santiago de Compostela Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Further, recent study proved that crambescidin 816 ( 80 ) could be stored into specialized sponge cells where it can be dispersed into the water affording a chemical umbrella surrounding the Crambe crambe sponge [ 77 ]. Recently, Botana and co-workers [ 78 ] reported important insights about the mechanism of the neurons cytotoxic activity of crambescidin 816 ( 80 ) in primary cultures of cortical neurons. These results showed that compound 80 is responsible for the decreasing of neuronal viability and hence provided a dose-dependent increase in cytosolic Ca 2+ level that was also linked to the presence of Ca 2+ in the extracellular media.…”
Section: Chemistry and Biology Of Natural Products Isolated From mentioning
confidence: 99%